Bankruptcy Law and Entrepreneurship - Armour, J; Cumming, D (2008)
Recent initiatives in a number of countries have sought to promote entrepreneurship through relaxing the legal consequences of personal bankruptcy. Whilst there is an intuitive link, relatively little attention has been paid to the question empirically, particularly in the international context. We investigate the relationship between bankruptcy laws and entrepreneurship using data on self-employment over 16 years (1990-2005) and fifteen countries in Europe and North America. We compile new indices reflecting how "forgiving" personal bankruptcy laws are. These measures vary over time and across the countries studied. We show that bankruptcy law has a statistically and economically significant effect on self-employment rates when controlling for GDP growth, MSCI stock returns, and a variety of other legal and economic factors. © The Author 2008. Published by Oxford University Press on behalf of the American Law and Economics Association. All rights reserved.